Charge profile analysis reveals that activation of pro-apoptotic regulators Bax and Bak relies on charge transfer mediated allosteric regulation - Ionescu, Crina-Maria; Svobodová Vařeková, Radka; Prehn, Jochen H M; Huber, Heinrich J; Koča, Jaroslav (PLoS computational biology, 2012)
The pro-apoptotic proteins Bax and Bak are essential for executing programmed cell death (apoptosis), yet the mechanism of their activation is not properly understood at the structural level. For the first time in cell death research, we calculated intra-protein charge transfer in order to study the structural alterations and their functional consequences during Bax activation. Using an electronegativity equalization model, we investigated the changes in the Bax charge profile upon activation by a functional peptide of its natural activator protein, Bim. We found that charge reorganizations upon activator binding mediate the exposure of the functional sites of Bax, rendering Bax active. The affinity of the Bax C-domain for its binding groove is decreased due to the Arg94-mediated abrogation of the Ser184-Asp98 interaction. We further identified a network of charge reorganizations that confirms previous speculations of allosteric sensing, whereby the activation information is conveyed from the activation site, through the hydrophobic core of Bax, to the well-distanced functional sites of Bax. The network was mediated by a hub of three residues on helix 5 of the hydrophobic core of Bax. Sequence and structural alignment revealed that this hub was conserved in the Bak amino acid sequence, and in the 3D structure of folded Bak. Our results suggest that allostery mediated by charge transfer is responsible for the activation of both Bax and Bak, and that this might be a prototypical mechanism for a fast activation of proteins during signal transduction. Our method can be applied to any protein or protein complex in order to map the progress of allosteric changes through the proteins' structure.
Keywords: biologické modely; apoptóza; interakční proteinové domény a motivy; sekvenční homologie aminokyselin; protein Bak; Protein Interaction Domains and Motifs; Sequence Homology, Amino Acid; počítačová simulace; Apoptosis; statická elektřina; sekvence aminokyselin; lidé; Molecular Sequence Data; Models, Biological; Amino Acid Sequence; protein X asociovaný s bcl-2; Computer Simulation; Models, Molecular; Computational Biology; molekulární sekvence - údaje; Protein Conformation; molekulární modely; alosterická regulace; konformace proteinů; bcl-2 Homologous Antagonist-Killer Protein; Allosteric Regulation; bcl-2-Associated X Protein; výpočetní biologie; Static Electricity; Humans